2021
DOI: 10.1111/trf.16746
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to red blood cell surface Glycophorin A impact the activation poise of circulating leukocytes

Abstract: Background Both M and N alleles encode antigens on Glycophorin A (GPA), a red blood cell (RBC) surface sialoglycoprotein. Interaction between RBC GPA and leukocyte surface lectins may downregulate their activation. The current study investigates if RBC autoantibodies against GPA, such as auto‐anti‐M/N, prime an activated phenotype in peripheral blood leukocytes. Methods Leukocyte activation was assessed in whole blood from patients with auto‐anti‐GPA (anti‐M/N) and compared to those with allo‐anti‐M/N and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…As shown previously, 7 , 8 whole blood-derived leukocytes are activated upon separation from RBCs. In light of the immunosuppressive properties of RBC transfusions in chronically transfused patients, 11 we evaluated if leukocyte activation could be reversed in vitro by suspending them with aliquots of RBCs either coated or not coated with anti-GPA.…”
Section: Methodssupporting
confidence: 70%
See 3 more Smart Citations
“…As shown previously, 7 , 8 whole blood-derived leukocytes are activated upon separation from RBCs. In light of the immunosuppressive properties of RBC transfusions in chronically transfused patients, 11 we evaluated if leukocyte activation could be reversed in vitro by suspending them with aliquots of RBCs either coated or not coated with anti-GPA.…”
Section: Methodssupporting
confidence: 70%
“… 14 , 15 , 16 CD63 expression from isolated monocytes separated from whole blood served as the reference activated control group, and we have previously shown that CD63 is significantly increased in isolated monocytes from buffy coats compared with monocytes in whole blood. 8 CD63 expression in isolated monocytes was suppressed by 26% after incubation with autologous RBCs ( n = 7 ) at a 1000:1 ratio ( P = .0464) ( Figure 4 A).
Figure 4.
…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Characterizing cell populations or immunophenotyping is a prevalent method for disease diagnosis from surface biomarkers using microfluidic arrays for label-free phenotyping [416] and interaction between RBC Glycophorin and leukocyte surface lectins activation [417].Other studies related to drug delivery assess the interaction mapping between RBCs and drug carriers via image analysis [418], capture and release of circulating tumor cells [419], drug-induced erythrocyte deformation [420], antibodies and biotinlabeled RBC effect on posttransfusion survival [421], shear-induced encapsulation in drug delivery [422], and anti-tumor applications incorporating RBCs and nanoparticles [423]. For COVID-19 related research, RBCs, as oxygen carriers, were analyzed for respiratory issues in COVID-19 patients for RBC deformability/morphology effect on tissues oxygen supply [424][425][426][427][428].…”
Section: Antibody Binding and Drug Discovery Applicationsmentioning
confidence: 99%